STRATEGI PENINGKATAN PAJAK DAERAH DI KABUPATEN KETAPANG - B61109059, JAMIL (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This research studies on regional tax Improvement Strategy in Ketapang. Problems in the analysis in this Research has pe are (1) how the effectiveness of tax revenue in Ketapang area; (2) What efforts have been made ​​to increase local tax revenue in Ketapang; (3) how the position of local taxes in Ketapang District; and (4) any constraints and obstacles encountered in increasing local tax revenue in the District Ketapang. Theoretical approach in this thesis rests pad a regional financial theory (Davey; 1988, Musgrave; 1993, Kaho, 1995, Mardiasmo; 2004 Official; 2007), and empirical approach refers to previous studies conducted by (Lains, 1995, Saragih; 1996, Lee and Snow; 1997, and Pause; 2000). The type of data that used is a time series (time series), while the data source consists of primary and secondary data. The analysis tool used is a quantitative and qualitative form of measurement of the effectiveness of tax collection, tax collection efforts, trouncing jat local independence, typology klassen and SWOT. The results of the analysis of the effectiveness, in the period of 2009-2013, Retained Earnings average local tax revenues in Ketapang very effective. The results of the analysis of k lassen typology of seven types of taxes that the object of research, there are no local taxes are categorized as excellent, there is one type of tax as a potential category, four types of taxes in developing categories, and two types categorized as retarded. The degree of financial independence in the category area Ketapang low. Efforts to improve tax collection has been carried out by the relevant agencies through programs and activities to improve infrastructure, increase the capability of personnel, coordination with parties related to local taxes, and dissemination of information about the local tax community. The results of Ana lysis SWOT, appropriate strategies to increase local tax revenue in Ketapang using SO strategy or strategies aggressive / expansive, which powers a whole strength and maximally exploit opportunities oriented on developing a way : (1) to optimized local regulations related to local tax revenues by leveraging the support of communication and media tools mas s a more advanced; (2) maximize the p rogram activities in raising local taxes revenue results by utilizing the ease of access to pay local taxes. Keywords: Â strategy of increasing local taxes, the effect tivity, tax effort, the degree to mandirian area.